PENGARUH KUALITAS AUDIT, INDEPENDENSI AUDITOR, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Qulub, Resky Ega Tatmainnul; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine out the influence of audit quality (KI), auditors independency (IA), firm size(SIZE), and profitability (PROFIT) to the earnings management (EM). Audit quality is proxy by the length ofthe correlation between the client and the auditor (audit tenure). Firm size is proxy by return on asset (ROA).Earnings management is proxy by the magnitude of discretionary accrual which has been done by usingmodified jones model. The sample is all retail trade companies which are listed in Indonesia Stock Exchange(IDX) in 2012-2015 periods. The sample collection technique has been done by using purposive sampling, sothat the samples are 10 companies with the amount of observation 40 firm years. The analysis method has beencarried out by using multiple linear regressions analysis with the instrument application is SPSS 20th version.The result of the research shows that audit quality and auditor independency give negative influence to theearnings management mean while firm size and profitability does not give any influence to the earningsmanagement.Keywords: Audit quality, auditor independency, firm size, profitability, earnings management.